Prevalence of Epstain–Bar Virus among Patients with Periodontitis in Al–Najaf Al–Ashraf / Iraq - AL-Yasseen, Ahlam; Alaa Shahid Jassim AL-Bdery (Al-Qadisiyah Journal of Pure Science, 2021)
Periodontitis, a complex chronic inflammatory disease caused by subgingival infection, is among the most prevalent microbial diseases in humans which characterized by periodontal damage, alveolar bone resorption, pain, and eventual tooth loss. Epstein–Barr Virus (EBV) has widely infected >90% adults in the world and is associated with many human diseases, so that this study aimed to investigate the association between EBV and periodontitis. Patients and samples: Subgingival paper point samples were collected from 100 patients with periodontitis and 30 healthy people. All samples undergo direct DNA extraction to amplified EBVs DNA using PCR technique. The results indicated a high percentage of EBV infections (18%) in patient suffering from periodontitis while there was no EBV infection were detected in healthy persons. A high percentage of EBV was detected in female (56%) in comparison with male (44%). The results improved the association between EBV and periodontitis suggesting that EBV may serve as a pathogenic factor leading to periodontitis among patients.